ChemInform Abstract: Arene C—H Bond Functionalization Coupling with Cyclization of Allenes. Issue 50 (10th December 2013) - Zeng, Rong; Ye, Juntao; Fu, Chunling; Ma, Shengming
Abstract A rhodium(III)‐catalyzed reaction of N‐methoxybenzamides with tri‐ and tetrasubstituted 2, 3‐allenols is developed to yield highly substituted 2, 5‐dihydrofurans (III) and (VI).